Ubiquitous Learning as Learning Method for Achieving Vocational Competencies in Higher Education During the Covid-19 Pandemic - Pratama Benny Herlandy; Hadi Purwanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Learning behavior at the higher education level has been disrupted more quickly since the outbreak of the Covid-19. The Student Centered Learning method which has become a culture in higher education cannot be implemented properly. The purpose of this study was to analyze the effectiveness of online learning by applying the ubiquitous learning method. The effectiveness in this study is to analyze the implementation of learning and the achievement of vocational competencies that can be achieved by students. The research was conducted using a quasi-experimental method. The sample in this study were students of the Informatics Education Strata 1 study program, Muhammadiyah University of Riau which consisted of 30 students in the control class and 30 students in the experimental class. The instruments used are learning outcomes tests, learning observations and questionnaires. The results obtained from the research, namely the ubiquitous learning method can be used in online learning at the Muhammadiyah University of Riau and in accordance with the learning information system that has been developed. The results of the ubiquitous learning effectiveness test in terms of the statistical test of the average comparison of the posttest results of the experimental and control classes were carried out, it was obtained that tcount = 3.425 ttable = 1.295 at a significance degree of 0.05. As a form of e-Learning learning method, U-Learning is able to help students to study and attend lectures in areas with low internet network infrastructure during the Covid-19 pandemic.